1982
DOI: 10.1002/art.1780251216
|View full text |Cite
|
Sign up to set email alerts
|

Selective immobilization of human mononuclear phagocytes by benoxaprofen

Abstract: Benoxaprofen [2-(4-chlorophenyl)-cu-methyl-5-benzoxazoleacetic acid] is a potent antiinflammatory agent that effectively suppresses edema and the infiltration of leukocytes in animal models of acute and chronic inflammation (1,2). Benoxaprofen has prevented the development of adjuvant arthritis in rats and reduced the intensity of established lesions of 14-25 days duration (1). The influx of mononuclear leukocytes into the pleural cavity of rats in response to injections of dextran or carrageenan was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition to preferential inhibitory activity for the enzyme 5'-lipoxygenase [4,5] benoxaprofen inhibits the migration of mononuclear leucocytes (MNL) from humans, rats and guinea-pigs in vitro [6,7]. The drug at therapeutic concentrations also inhibits the random and leucoattractant-induced migration of human polymorphonuclear leuco- [1,7]. We have previously reported that benoxaprofen, unlike other nonsteroidal anti-inflammatory drugs (NSAID's), increases the spontaneous membrane-associated oxidative metabolism of human PMNL in vitro [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to preferential inhibitory activity for the enzyme 5'-lipoxygenase [4,5] benoxaprofen inhibits the migration of mononuclear leucocytes (MNL) from humans, rats and guinea-pigs in vitro [6,7]. The drug at therapeutic concentrations also inhibits the random and leucoattractant-induced migration of human polymorphonuclear leuco- [1,7]. We have previously reported that benoxaprofen, unlike other nonsteroidal anti-inflammatory drugs (NSAID's), increases the spontaneous membrane-associated oxidative metabolism of human PMNL in vitro [1].…”
Section: Introductionmentioning
confidence: 99%
“…acetylsalicylic acid (Goetzl & Valone 1982) and indomethacin (Goetzl & Valone 1982;Nielsen & Bennedsen 1982), do not suppress monocyte chemotaxis. In contrast, inhibitors of lipoxygenase activity often inhibit leukotaxis (Goetzl & Valone 1982). Fenflumizole has been shown to exert some lipoxygenase inhibitory activity (Broodley, personal communication), which may explain its influence on monocyte migration as well.…”
mentioning
confidence: 99%
“…The inhibitory effect is insufficiently explained by its cyclooxygenase inhibitory activity, since NSAIDs with classical cyclooxygenase inhibitory activity, e.g. acetylsalicylic acid (Goetzl & Valone 1982) and indomethacin (Goetzl & Valone 1982;Nielsen & Bennedsen 1982), do not suppress monocyte chemotaxis. In contrast, inhibitors of lipoxygenase activity often inhibit leukotaxis (Goetzl & Valone 1982).…”
mentioning
confidence: 99%